Age dependent treatment response to the Carriere ® Motion 3D ™ appliance for the correction of Class II malocclusion - Malinowski, Klara; Chodur, Monika; Majewski, Maciej; Malinowski, Jakub (Journal of Education, Health and Sport, 2022)
Introduction and Purpose Class II malocclusion is a common anomaly. Both adults and adolescents with Class II malocclusion can be treated. One of the methods for correction is Carriere ® Motion 3D ™ appliance (CMA). The aim was to evaluate and compare the rate of tooth movement depending on age during treatment with Carriere ® Motion 3D ™ appliance (CMA). Material and method The retrospective study investigated medical records of 28 adult and 27 adolescent subjects who were treated with the Carriere ® Motion 3D ™ distalizer to correct Class II malocclusion. Time (in days) needed to achieve 1 mm correction was calculated for each patient, based on the quotient of days needed for Class II correction and the distance required to achieve Class I canine relationship. The difference between groups was analyzed using the Mann-Whitney-U test. Results Phase I treatment with CMA lasted on average 5,67 ± 2,01 months for adults and 4,67 ± 1,48 months for teenagers. The mean time to achieve 1 mm correction was 36,77 ± 11,01 days in the adult group and 36,59 ± 26,17 days in the adolescent group. The results showed no statistically significant difference between the two groups. Conclusions CMA can be applied to efficiently treat Class II malocclusion in adolescent as well as adult patients. No difference in age related tooth movement using the CMA was found.